Combustion characteristics of hydrogen direct injection in a helium–oxygen compression ignition engine. (November 2022) - Taib, Norhidayah Mat; Mahmood, Wan Mohd Faizal Wan; Mansor, Mohd Radzi Abu
Abstract: The ignition of hydrogen in compression ignition (CI) engines by adding noble gas as a working gas can yield excellent thermal efficiency due to its high specific heat ratio. This paper emphasizes the potential of helium–oxygen atmosphere for hydrogen combustion in CI engines and provides data on the engine configuration. A simulation was conducted using Converge CFD software based on the Yanmar NF19SK engine parameters. Helium–oxygen atmosphere compression show promising hydrogen autoignition results with the in-cylinder temperature was significantly higher than that of air during the compression stroke. In a compression ignition engine with a low compression ratio (CR) and intake temperature, helium–oxygen atmosphere is recognized as the best working gas for hydrogen combustion. The ambient intake temperature was sufficient for hydrogen ignition in low CR with minimal heat flux effect. The best intake temperature for optimum engine efficiency in a low CR engine is 340 K and the engine compression ratio for optimum engine efficiency at ambient intake temperature is CR12 with an acceptable cylinder wall heat flux value. The helium–oxygen atmosphere as a working gas for hydrogen combustion in CI engines should be consider based on the parameter provided for clean energy transition with higher thermal efficiency.